2021
DOI: 10.3390/jrfm14100474
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Bank Failures: A Synthesis of Literature and Directions for Future Research

Abstract: Risk management has been a topic of great interest to Michael McAleer. Even as recent as 2020, his paper on risk management for COVID-19 was published. In his memory, this article is focused on bankruptcy risk in financial firms. For financial institutions in particular, banks are considered special, given that they perform risk management functions that are unique. Risks in banking arise from both internal and external factors. The GFC underlined the need for comprehensive risk management, and researchers sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 75 publications
(100 reference statements)
1
6
0
Order By: Relevance
“…Although many works have been proposed to solve financial crisis prediction issues [ 1 , 15 33 ], very little work has used the concept of Explainable Artificial Intelligence (XAI) in predicting financial crises. The first question in this study sought to determine the most important features which have a big influence in predicting a financial crisis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although many works have been proposed to solve financial crisis prediction issues [ 1 , 15 33 ], very little work has used the concept of Explainable Artificial Intelligence (XAI) in predicting financial crises. The first question in this study sought to determine the most important features which have a big influence in predicting a financial crisis.…”
Section: Discussionmentioning
confidence: 99%
“…The literature on Artificial Intelligence to predict financial crisis roots has highlighted several techniques and methodologies [ 1 , 15 17 ]. Over the past decade, most research has emphasized machine learning techniques to solve financial crisis forecasting problems.…”
Section: Related Workmentioning
confidence: 99%
“…In the banking literature, the variables that reflect bank fundamentals are CAMEL variables, which relate to management, capital adequacy, efficiency, management, and earnings. Indeed, a comprehensive set of recent studies confirmed the early findings that these indicators are good predictors of bank failure (Liu et al, 2021;De Haan et al, 2020;Bongini et al, 2018). Accordingly, we suggest our second hypothesis: Hypothesis 2: BETA depends significantly on the CAMEL variables.…”
Section: Literature Review and Hypotheses Developmentsupporting
confidence: 78%
“…The results show high predictive power of Z-score model which can guide financial managers, auditors, and investors to take decisions wisely. Liu et al (2021) synthesize the literature on bank failure prediction. According to the authors, the bank failure prediction power of statistical techniques is very limited.…”
Section: Literature Reviewmentioning
confidence: 99%